Taxonomic notes on Western Palaearctic Conopidae (Diptera) - Stuke, Jens-Hermann (Zootaxa, 2016)
Twenty-three new synonyms are introduced and one species is placed as nomen dubium in the conopid genera Conops, Myopa, Physocephala and Thecophora. Myopa fasciata is designated as the type species of Ischiodonta Lioy. Dipodium apiarium Bosc d’Antic is interpreted as an unrecognised species and therefore Dipodium Bosc d’Antic also has to be treated as an unrecognised genus. A key to the Western Palaearctic species of Physocephala is provided.